The Implementation of Dicovery Role Play in the Nervous System Learning at Senior High School - Sa'diyyah, Ida Himmatus; Setiati, Ning; Lisdiana, Lisdiana (Journal of Biology Education, 2020)
This study aims to implement the discovery of roleplay on nervous system material in senior high school. This research is a Quasi-Experimental research which is conducted in January - October 2018 in the Biology Department FMIPA Semarang State University and MA Matholi'ul Falah Demak. The sampling technique uses purposive sampling. The Research data in the form of learning outcomes, communicative characters, student responses, and teacher interviews. The student learning outcomes data in the form of cognitive aspects of the results of the data are analyzed by t-test and communicative character data are analyzed using descriptive percentages. The results show that the average value of cognitive learning outcomes is 83.32 and 75.32, the results of the t-test are 0.001, indicating that there are significant differences in results between the experimental class and the control class. The results of the communicative character of students were 92% with very good criteria. The conclusion of this study is the implementation of discovery role play affects the learning outcomes and the formation of the communicative character of students in nervous system material in senior high school.